Diving mask adapted for non-invasive ventilation and prone position in a patient with severe covid-19: case report - Wagner, Litiele Evelin (2020)
Justification and objectives: In the search of strategies to treat acute respiratory failure caused by COVID-19, non-invasive ventilation (NIV) and the use of prone position in spontaneous breathing appear. The objective is to present the case of a patient with severe COVID-19 admitted to an intensive care unit (ICU) who used an adapted diving mask, which is configured as an innovative interface for NIV, and the prone position. Methods: Case report of a hospitalized patient diagnosed with COVID-19 who underwent early NIV by means of an adapted diving mask and the prone position during spontaneous breathing for 8 hours at night and 6 hours in the day. Results: Female patient, 56 years old, systemic arterial hypertension and obesity, with dry cough, odynophagia, fatigue and severe dyspnea on admission. Chest tomography with bilateral ground-glass opacities. Non-invasive ventilation was instituted 1-2.75 times/day, for 40-60 minutes, with positive pressure at the end of expiration of 8 (7.25-8.00) cmH2O and support pressure of 5.5 (4.00 -6.00) cmH2O. Air leaks of 6 to 30%, with good tolerance. The prone position during spontaneous breathing resulted in increased peripheral oxygen saturation and reduced respiratory discomfort 30 minutes later. Conclusion: The association of the use of NIV with an adapted diving mask and prone position during spontaneous breathing proved to be effective in preventing the orotracheal intubation of a patient with severe COVID-19, emphasizing the importance of the proposed intervention.